A participatory framework for feasibility assessments of climate change resilience strategies for smallholders: lessons from coffee cooperatives in Latin America. Issue 1 (2nd January 2020) - Shapiro-Garza, Elizabeth; King, Danielle; Rivera-Aguirre, Ariadne; Wang, Sapphire; Finley-Lezcano, Jennifer
ABSTRACT: Coffee farmers are already experiencing the impacts of climate change, yet recommended resilience strategies are often cost-prohibitive for smallholder producers and/or maladapted to local conditions and contexts. We collaborated with smallholder coffee cooperatives in Latin America to assess the feasibility of climate change resilience strategies they selected: crop diversification; rainwater collection systems; pest monitoring and management; collective coffee seed banks and nurseries; and solar coffee dryers. Data was collected through key actor and cooperative leader semi-structured interviews and focus groups with cooperative members. Our results provide criteria that can be used to determine if these five resilience strategies are appropriate for given environmental, socioeconomic, and political contexts. They also demonstrate the need for tailoring resilience strategies to fit local conditions. The framework we applied serves to select appropriate, effective and equitable resilience strategies, combining a participatory action research approach to incorporate local knowledge, capital assets analysis for a holistic and realistic understanding of feasibility, and access analysis for an assessment of who will benefit and who will not. This framework can be applied to assess the feasibility of climate change resilience strategies with smallholders in a wide variety of geographies, contexts and agroecosystems.